Realizing Decent Work in a "Sandwich" Position: Assessing VET Trainers' Working Conditions in Times of Multiple Transformations - Manuel Nicklich; Marco Blank; Sabine Pfeiffer (International Journal for Research in Vocational Education and Training)
Context: The German vocational training and education (VET) system is designed to cope with change. Within this system, organizational VET trainers (OVETT) are the main persons of reference for apprentices in the organization, in most cases for the whole three-year training period. Whether training can help to realize or maintain decent work also depends on whether the trainers themselves have decent working conditions.